2006
DOI: 10.1142/s0218195906001999
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Geometric Approaches for Leaf Sequencing Problems in Radiation Therapy

Abstract: The 3-D static leaf sequencing (SLS) problem arises in radiation therapy for cancer treatments, aiming to deliver a prescribed radiation dose to a target tumor accurately and efficiently. The treatment time and machine delivery error are two crucial factors to the solution (i.e., a treatment plan) for the SLS problem. In this paper, we prove that the 3-D SLS problem is NP-hard, and present the first ever algorithm for the 3-D SLS problem that can determine a tradeoff between the treatment time and machine deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…(A constant window function W (·) is defined on an interval I such that W (x) is a fixed value h > 0 for any x ∈ I and is 0 otherwise.) Since the shape rectangularization problems are NP-hard [7,8] (in fact, APX-hard [1]), approximation algorithms were given, and some special cases were solved optimally [1,7]. Note that constant window functions are a more restricted form of unimodal functions.…”
Section: Motivations and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…(A constant window function W (·) is defined on an interval I such that W (x) is a fixed value h > 0 for any x ∈ I and is 0 otherwise.) Since the shape rectangularization problems are NP-hard [7,8] (in fact, APX-hard [1]), approximation algorithms were given, and some special cases were solved optimally [1,7]. Note that constant window functions are a more restricted form of unimodal functions.…”
Section: Motivations and Related Workmentioning
confidence: 99%
“…It is also interesting to note that while the unimodal representation problems are nearly linear time solvable, in contrast, the shape rectangularization problems, which can be viewed as a more restricted case of the unimodal representation problems, are NP-hard [1,7,8].…”
Section: Our Contributionsmentioning
confidence: 99%
“…They also discuss further improvements of the formulation through cuts and bounds. Chen et al (2004aChen et al ( ,b, 2005Chen et al ( , 2006 consider the decomposition cardinality problem with interleaf motion, width, and tongue-and-groove constraints. The first two groups of constraints are considered by a geometric argumentation.…”
Section: Theorem 16mentioning
confidence: 99%
“…Baatar et al [9] showed that NP-hardness holds for input IMs even with a single row, using a reduction from the 3-partition problem [20]. Chen et al [16], independently, gave an NP-hardness proof of this problem based on a reduction from the 0-1 knapsack problem [20]. The GSR problem, as a generalization of the SR problem, is clearly NP-hard.…”
Section: Previous and Related Workmentioning
confidence: 99%